SHAKESPEARE’S TROILUS THROUGH FEMINISM - Dubey, Yogesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present paper attempts to examine the character of Shakespeare’s Troilus from Troilus and Cressida in the light of feminism. Though a number of studies have been conducted on the play with special focus on the character of Troilus but finding them lacking in the feminist perspective either entirely or not sufficiently enough this study undertakes to establish Troilus as a weak, emotional and feminine male.